Non isolated coupled converter tied voltage source inverter drive - A. Suresh Kumar; R. K. Pongiannan; C Bharatiraja; Adedayo Yusuff; N Yadaiah (Institute of Advanced Engineering and Science, 2019)
The voltage source inverters (VSI) are ever required section in the AC motor drive and power system interface. The electrical drive segment, the VSI based drives are unavoidable and they are closely operated with induction motor, permanent magnate synchronous motor and BLDC motor. These drives are normally needed high torque-power characters. Hence, the input DC-link side voltage is increased with help of increasing input AC in the rectifier input. However, this causes the power quality disturbance in the AC main and DC-link. In order to go for a increasing the AC voltage, the rectifier out is connected with DC to DC boost converter and they are increasing the DC voltage to meet out the drive DC-link voltage demand. With this aim, the paper proposes the idea to connect high step non-isolated high gain coupled DC to DC converter with three phase VSI for drives applications. The proposed converter has an ability to increase the voltage five times and the counter winding arrangement ratio of the converter is help for the further increase of gain. Inn this interface the front end DC to DC converters inductors are charged by making the short circuit with inverter switching. The converter voltage gain is controlled by shoot through of the VSI switch (converter gain directly proportional to inverter shoot through). The proposed converter has a higher degree of freedom in their values of winding and output voltage. Hence, the DC-link voltage of the inverter can be extended in any level. The operation principle and modes of the proposed DC to DC Source tied VSI is analyzed and simulated using MATLAB-Simulink software simulation. The laboratory based small scale power circuit is developed with help of control algorithm. The entire implementation is done through PIC microcontroller platform. The deign Investigation, system simulation and experimentation confirming the proposed DC to DC converter tied VSI drive system.